Prevalence of bacteriocins and their co-association with virulence factors within Pseudomonas aeruginosa catheter isolates - Dufková, Kristýna (Jihočeská univerzita, 2021)
Urinary tract infections caused by Pseudomonas aeruginosa present a serious complication in the context of urinary catheter use. P. aeruginosa are equipped with various virulence determinants that may result in increased resistance. That contributes to higher morbidity and mortality in vulnerable patients. Pyocins are proteinaceous agents produced by pseudomonads with an antimicrobial effect targeting closely related bacteria. In this study, we examined the inhibition interactions among a set of 135 P. aeruginosa clinical isolates originated from the catheter-associated urinary tract infections. Togerther with pyocinogeny, the co-occurrence of other virulence factors and their co-association with pyocins were examined. The strong antagonistic interactions and high prevalence of pyocin genes among the isolates were observed. The overall competitive interactions provide promising findings in the area of alternative antibiotic approaches.
Prevalence of bacteriocins and their co-association with virulence factors within Pseudomonas aeruginosa catheter isolates
Keywords: bacteriocin; pyocin; Pseudomonas aeruginosa; CAUTI; siderophores; bacteriocin; pyocin; Pseudomonas aeruginosa; CAUTI; siderophores